Pengaruh Likuiditas dan Aktivitas Terhadap Financial Distress Dengan Profitabilitas Sebagai Variabel Moderasi Pada Perusahaan Food & Beverage yang Terdaftar di BEI Periode 2017-2022 - Indah Nur Asmiraldha; Liza Novietta; Ruswan Nurmadi (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2024)
This research aims to know the influence of Liquidity and Activity on Financial Distress with Profitability as a Moderating. The population used in this research is a food & beverage sub sector companies listed on the Indonesia Stock Exchange (IDX) for the 2017-2022 period. This type of research is an associative study using quantitative method. The sampling is conducted using the purposive sampling technique. The number of samples in this research are 28 companies out of 45 population for six years of observation. As a result, a total of 168 data observation samples were obtained. The analysis technique used in this research are logistic regression and MRA (Moderated Regression Analysis). The results showed that Liquidity had a negative and significant effect on Financial Distress, Activity has no effcet on Financial Distress. Profitability can moderate the influence of Liquidity on Financial Distress but cannot moderate the influence of Activity on Financial Distress at food & beverage sub sector companies listed on the Indonesia Stock Exchange for the 2017-2022 periode.